A cyclophilin links redox and light signals to cysteine biosynthesis and stress responses in chloroplasts - Dominguez-Solis, Jose R. (National Academy of Sciences, 2008)
Cyclophilins belong to a large family of enzymes called “peptidyl prolyl isomerases” that assist protein folding and assembly. The cyclophilin CYP20–3 (also known as “ROC4”) is the only member of this group located in the stroma (soluble phase) of chloroplasts. In the present study we isolated mutant Arabidopsis plants defective in the CYP20–3 gene and found them to be hypersensitive to oxidative stress conditions created by high light levels, rose bengal, high salt levels, and osmotic shock. Chloroplast serine acetyltransferase (SAT1), a rate-limiting enzyme in cysteine biosynthesis, was identified as an interacting partner for CYP20–3 by protein interaction analyses. In the present experiments, SAT1 activity increased significantly under conditions of light and oxidative stress in concert with total thiols in wild-type plants. By contrast, these parameters changed only marginally in experiments with the cyp20–3 mutant, suggesting that CYP20–3 links light and stress to SAT1 activity and cysteine biosynthesis. In further support of this conclusion, our analyses showed that the salt-hypersensitive phenotype of the mutant developed under illumination and not in the dark. Together with the earlier report that CYP20–3 foldase activity is enhanced by thioredoxin-mediated reduction, our findings suggest that CYP20–3 links photosynthetic electron transport and redox regulation to the folding of SAT1, thereby enabling the cysteine-based thiol biosynthesis pathway to adjust to light and stress conditions.